Extreme shear deformation enables ultra-fast riveting of high strength aluminum alloys. (March 2022) - Wang, Tianhao; Gwalani, Bharat; Song, Miao; Ma, Xiaolong; Liu, Tingkun; Das, Hrishikesh; Silverstein, Joshua; Whalen, Scott
Abstract: Dispersed nano-precipitates strengthen high-strength aluminum (Al) alloys but reduce ductility and formability. Joining these alloys with conventional impact (or driven) riveting has long been a challenge because the rivets may crack in ambient conditions. Rotating hammer riveting (RHR) was developed to rivet fully hardened high-strength Al alloys 2024-T351 and 7075-T6. RHR eliminates the need to soften 7075 rivets by preheating or to store 2024 rivets at low temperature to preserve the annealed condition. Avoiding cracked rivet heads and shanks during RHR is attributed to high-strain-rate plastic deformation, which promotes dynamic recrystallization of grains and amorphization of second phases; this mitigates stress concentration and prevents microvoids. Meanwhile, the coherent solute atom clusters in the Al matrix are sheared by dislocation movement, not coarsened, because the thermal cycle is short (10 −1 s). RHR obviates time- and cost-intensive prior and post-processing heat treatments, achieving high integrity between riveted and assembled components.